Gambaran Sanitasi Dasar Di Desa Meranti Kabupaten Asahan - Meutia Nanda; Dina Zairina Rizky; Fauza Tamara; Ila Azlina Sinaga; Dian Anggreni; Dina Anggraini; Devi Pratiwi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Basic sanitation efforts include the provision of clean water, disposal of human waste (latrines), waste management and sewerage.The purpose of this research is to see the description of basic sanitation conditions as an effort to improve environmental health in the village. The type of research used is descriptive observational research with a cross-sectional approach. The population in this study were people aged 18 years and over who lived and settled in Meranti Village. The total sample in this study was 145 samples with random sampling. The survey results found that there was still a lot of open public bathroom waste water disposal, namely (37.2%) of which (22.1%) disposed of groundwater infiltration or without drainage. There are (96.6%) respondents already using latrines, (88.3%) managing household waste by burning, and almost all of them have good sources of clean water (96%). In conclusion,the provision of waste disposal facilities and waste management has not been carried out properly, this is a big risk for the 10 highest types of diseases in Meranti Village.